Factors Affecting Male Involvement in Family Planning at Kazo Health Center IV in Kazo Town Council Kazo District. - Ndyaguma, Laban (Kabale University, 2023)
The study was about factors affecting male involvement in family planning at kazo health center iv in Kazo town council Kazo district. The study was guided by the following study objectives: To find out the level of male involvement family usage, relationship between male involvement and family planning utilization and to devise means of increasing male involvement in family planning in Kazo town council . A cross sectional research design was used for this study where both quantitative and qualitative methods were employed, the population of the study included Women, Men, health staff and local leaders. The study revealed that there is low involvement in family planning to the extent that some men have never a companied their wife to the family planning clinic, claiming that they have no time to escort their wives for family planning saying that they are busy looking for money than going with their wives to clinics, more still men some lack information about the use of family planning other than use of condoms. Also male involvement in family planning has a positive influence in their utilization when male involvement increases family planning utilization among married couples increases and vise verse. Among the views pointed out by the respondent's on men's participation in family planning as highlighted in the study also agreed with the related literature like culture factors, religious beliefs, social economic factors and psychological factors, Also suggested some other reasons like Ignorance lack of time false myth and fear of family planning side effects as mentioned by the majority of respondents as discussed during a focus group discussion where they mentioned that condoms cause cancer. Men need more information and education so that they can fully participate in family planning services, support their partners and utilize the services and that Health care providers should conduct workshops or hold social gatherings and inform men about family planning and its importance. On recommendation the government should establishment of men's clinics so that men can feel free to go and utilize the services. The services should be user friendly to men in order to be utilized to the maximum Male only clinics should inform men about all family planning methods and provide condoms and vasectomy and counsel men with respect and sensitivity, more so Education, men need a lot of information on family planning so that they are well informed.